Formulation and optimization of raloxifene loaded nanotransfersomes by response surface methodology for transdermal drug delivery - Mahmood, Syed; Bakhtiar, M. Taher; Mandal, Uttam Kumar (2014)
Raloxifene HCl belongs to selective estrogen receptor modulators (SERM), structurally similar to estrogen with important effects on reproductive and many non-reproductive tissues. It is highly recommended by medical practitioners for the treatment of breast cancer, osteoporosis, and postmenopausal symptoms. It is mostly administered at a total dose of 60 mg tablet daily. However the major obstacle for the oral delivery of raloxifene is poor systemic exposure with only 2% absolute bioavailability because of its poor solubility in aqueous fluids and extensive first pass metabolism [1, 2]. Transfersome is an ultra-deformable vesicle which is composed of an aqueous core surrounded by a combination of lipid and surfactant. Unlike the conventional liposome, presence of surfactant makes transfersome an ultra-deformable, self- regulating, highly adaptable, and stress responsive complex aggregate [3]. Raloxifene loaded transfersomes were fabricated, optimized and characterized as carrier for transdermal delivery to overcome the poor bioavailabilty issue with this drug. Drug loaded transferosomal vesicles were prepared with phospholipon 90G (PC 90G) as structural phospholipid and sodium deoxycholate (SDC) as edge activator/surfactant by conventional thin-layer rotary evaporation method [4]. Response surface methodology (RSM) was applied for the optimization of formulation using Box-Behnken experimental design. Phospholipid PC90G (A), SDC (B) and sonication time (C), each at three levels, were selected as independent variables while entrapment efficiency (EE%) (Y1), vesicle size (Y2), and transdermal flux (Y3) were the response variables. In-vitro release and permeation of raloxifene from the transfersomal formulations were measured by Hanson diffusion cell using rat skin as barrier membrane. Amount of drug present in test samples during entrapment efficiency and in-vitro permeation study was determined by a validated HPLC method. Seventeen (17) trial formulations at various factors combinations including five centre points were prepared according to the Box-Behnken experimental design as shown in Table 1. Various RSM computations were performed by Design expert® software (version 8.0.7.1, stat-Ease Inc., Minneapolis, MN). Polynomial models including interaction and quadratic terms were generated for all response variables using multiple linear regression analysis (MLRA) approach. Response surface graphs (3-D) and two dimensional (2-D) contour plots were generated in order to evaluate the effects of individual independent variables on response variables. The optimized formulation as predicted by RSM was then further characterized for vesicular size distribution, shape, surface morphology, and zeta-potential. Conventional liposomes consisting of raloxifene were also prepared by mechanical dispersion to compare transdermal flux with that of transfersomes [5]. Coumarin-6 (0.03% w/v) loaded transfersomes and liposomes were prepared for confocal laser scanning microscopy (CLSM) study. Six-point standard curve in the range of 0.125 to 5 µg/ml by HPLC was found to be linear with correlation coefficient 0.999 (calibration equation y = 76.082x + 8.466). Representative chromatogram of a sample analysed for in-vitro drug permeation study is shown in Fig. 1. TEM, DLS defined transfersomes as spherical, unilamellar structures with a homogenous distribution and low polydespersity index (PDI) (0.080±0.021). Visualization of transfersomes by SEM also proved the same finding (Fig. 2). The results of entrapment efficiency (EE%) (Y1), vesicle size (Y2), and transdermal flux (Y3) are presented in Table 1. After analyzing the response variables data by Design expert® software, the best model for all three response variables was found to be quadratic. Mathematical relationship generated using MLRA for the studied response variables are expressed as following equation 1 to 3.